Ionic liquid- and surfactant-controlled crystallization of WO3 films1. Issue 27 (21st July 2015) - Kaper, Helena; Djerdj, Igor; Gross, Silvia; Amenitsch, Heinz; Antonietti, Markus; Smarsly, Bernd M.
<x xml:space="preserve">Abstract</x> Colorful structures: ionic liquids (C16mimCl) direct the crystallographic orientation in the sol–gel-based synthesis of WO3 films, improving electrochromic behavior.